2010
DOI: 10.1016/j.dld.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic IgG/IgM plasma cells ratio helps in classifying autoimmune liver diseases

Abstract: Immunostaining for IgM and IgG plasma cells on liver tissue can be a valuable parameter for better diagnosis of autoimmune liver disease and also for variant or mixed syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
2
20
1
Order By: Relevance
“…Furthermore, we used CD138, a highly sensitive and specific marker of plasma cells, for rapid and precise localization of plasma cells, unlike the previous reports. Recent reports suggest that the IgM/IgG ratio could be used to distinguish PBC from AIH [10,11]. This is supported by our results, which revealed a significantly higher IgM/IgG ratio in patients with PBC compared to those with AIH or OS (0.2, 2.0, and 0.3, P \ 0.005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we used CD138, a highly sensitive and specific marker of plasma cells, for rapid and precise localization of plasma cells, unlike the previous reports. Recent reports suggest that the IgM/IgG ratio could be used to distinguish PBC from AIH [10,11]. This is supported by our results, which revealed a significantly higher IgM/IgG ratio in patients with PBC compared to those with AIH or OS (0.2, 2.0, and 0.3, P \ 0.005).…”
Section: Discussionsupporting
confidence: 91%
“…Plasma cells are characteristically found in AIH, but are also commonly present in PBC. Recent studies have shown that it is possible to distinguish AIH from PBC with periportal plasmacytic infiltrates by IgG and IgM immunohistochemistry (IHC) [8][9][10][11]. Although most immunohistochemical markers are not completely satisfactory for use in histological biopsy sections, some have the potential to improve the specificity and sensitivity of plasma cell detection, including CD138 antibodies [12].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, results of staining for IgG and IgM in putative cases AIH-PBC overlap were inconsistent, and the specificity and sensitivity of immunostaining to detect AIH or PBC were low [114]. Importantly, PBC was exclusively associated with a ratio of IgG to IgM expressing plasma cells < 1, while a ratio > 1 was present in the patients with putative AIH overlap [115].…”
Section: Aih-pbc Overlap Syndromementioning
confidence: 92%
“…A recent cross-sectional study reported that Hispanic patients with PBC had a significantly increased prevalence of overlap syndrome compared with non-Hispanic PBC patients (31% vs. 13%; P = 0.002) [113], suggesting an ethnic predisposition. Immunohistochemical staining of plasma cells expressing IgG or IgM in liver biopsies has been proposed as an aid in the diagnosis of AIH-PBC overlap [114,115]. Plasma cells predominantly express IgG in AIH and IgM in PBC; thus, concurrent expression of both would suggest overlap.…”
Section: Aih-pbc Overlap Syndromementioning
confidence: 99%
“…Another study reported that the frequency of HLA-DR7 was increased in AIH-PBC overlap, possibly conferring increased susceptibility [36]. Immunostaining of liver biopsies for plasma cells expressing IgG or IgM was proposed as an aid in the diagnosis of PBC-AIH overlap [37,38]. Plasma cells in AIH predominantly express IgG, while plasma cells in PBC predominant express IgM.…”
Section: Overlap Syndromesmentioning
confidence: 99%